2014
DOI: 10.1038/oncsis.2014.26
|View full text |Cite
|
Sign up to set email alerts
|

Selective repression of the oncogene cyclin D1 by the tumor suppressor miR-206 in cancers

Abstract: MicroRNAs (miRNAs) are deregulated in cancer and have been shown to exhibit both oncogenic and tumor suppressive functions. Although the functional effects of several miRNAs have been elucidated, those of many remain to be discovered. In silico analysis identified microRNA-206 (miR-206) binding sites in the 3′-untranslated regions (3′-UTR) of both the mouse and human CCND1 gene. Cyclin D1 is a recognized oncogene involved in direct phosphorylation of the retinoblastoma (Rb) protein and promoting cell cycle tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 24 publications
3
34
0
Order By: Relevance
“…Several investigations have demonstrated that decreased miR-206 expression is involved in breast cancer proliferation [43, 44]. Our previous studies show that miR-206 is antagonistically involved in TNBC invasion and angiogenesis through modulating VEGF and MAPK3 [35].…”
Section: Discussionmentioning
confidence: 99%
“…Several investigations have demonstrated that decreased miR-206 expression is involved in breast cancer proliferation [43, 44]. Our previous studies show that miR-206 is antagonistically involved in TNBC invasion and angiogenesis through modulating VEGF and MAPK3 [35].…”
Section: Discussionmentioning
confidence: 99%
“…It has been found to be down-regulated in ERα-positive BC, both in patient samples and BC cell lines [61], and in lymph node metastatic BC [62]. A critical role of Hsa-miR-206 has been recently demonstrated in the regulation of the 3′ UTR of cyclin D1, inducing G1 arrest and a decrease in cell proliferation in BC cells [63], thus suggesting a potential role as a tumour suppressor. It has been also shown that Hsa-miR-206 regulates ERα via interaction with its 3′ UTR [64], demonstrating a specific function in most aggressive types of BC.…”
Section: Introductionmentioning
confidence: 99%
“…As was expected, miR-206 modulates gene expression by the direct binding oftarget mRNA3 0 -UTR. miR-206 could specifically bind to the CCND1 3 0 -UTR and reducecyclin D1 expression, resulting inG1 arrest induction andproliferation inhibition in breast cancer cells [16].Emerging evidence has shown that miR-206 is involved in glucose metabolic reprogramming. miR-206 expression was demonstrated to be inversely correlated with pentose phosphate pathway (PPP) gene expression [17].…”
Section: Introductionmentioning
confidence: 99%